EXPERIENCE OF USING CLOUD COMPUTING IN NETWORK PRODUCTS FOR SCHOOL EDUCATION - Sokolova, Л.Е.; Olevskii, В.И.; Olevskaya, Ю.Б. (Journal of Information Technologies in Education (ITE), 2011)
We study data on the use of sites in the middle grades, secondary school, and their influence on the formation of information culture of students and their level of training. Sites use a technology called "cloud computing in Google, accessible from any internet-connected computer and do not require the use of resources of the computer itself. Sites are devoid of any advertising, does not require periodic backup, protection and general operation of the system administrator. This simplifies their use in the educational process for schools of different levels. A statistical analysis of the site was done, identified the main trends of their use.